Antecedentes poblacionales de Chaptalia exscapa (Pers.) Baker var. chilensis (DC.) Burkart en la provincia de Talca, Chile central - Gómez, Persy; Hahn, Steffen; San Martín, José; Belov, Michail (Gayana Botánica, 2015)
We examine the distribution and ecology of Chaptalia exscapa (Pers.) Baker var. chilensis (DC.) Burkart in the Talca Province, Maule Region. It is reports new data related to the morphology of the plant and the presence of Chaptalia in four new localities in the Maule Region. The populations present a high vulnerability due low population size and disturbed habitat. Flowering and fructification of individuals is scanty.